The majority of Swedish systemic lupus erythematosus patients are still affected by irreversible organ impairment: factors related to damage accrual in two regional cohorts. (September 2019) - Frodlund, M; Reid, S; Wetterö, J; Dahlström, Ö; Sjöwall, C; Leonard, D
Background: Although the survival of patients with systemic lupus erythematosus (SLE) has improved, irreversible organ damage remains a critical concern. We aimed to characterize damage accrual and its clinical associations and causes of death in Swedish patients. Methods: Accumulation of damage was evaluated in 543 consecutively recruited and well-characterized cases during 1998−2017. The Systemic Lupus International Collaborating Clinics (SLICC)/American College of Rheumatology damage index (SDI) was used to estimate damage. Results: Organ damage (SDI ≥ 1) was observed in 59%, and extensive damage (SDI ≥ 3) in 25% of cases. SDI ≥ 1 was significantly associated with higher age at onset, SLE duration, the number of fulfilled SLICC criteria, neurologic disorder, antiphospholipid antibody syndrome (APS), hypertension, hyperlipidemia, depression and secondary Sjögren's syndrome (SS). In addition, SDI ≥ 3 was associated with serositis, renal and haematological disorders and interstitial lung disease. A multiple regression model identified not only well-known risk factors like APS, antihypertensives and corticosteroids, but pericarditis, haemolytic anaemia, lymphopenia and myositis as being linked to SDI. Malignancy, infection and cardiovascular disease were the leading causes of death. Conclusions: After a mean SLE duration of 17 years, the majority of today's Swedish SLE patients have accrued damage. We confirm previous observations and report some novel findings regarding disease phenotypes and damage accrual.